2005
DOI: 10.1074/jbc.m409020200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Changes in the Evolution of Type II Restriction Endonucleases

Abstract: How restriction enzymes with their different specificities and mode of cleavage evolved has been a long standing question in evolutionary biology. We have recently shown that several Type II restriction endonucleases, namely SsoII (2CCNGG), PspGI (2CCWGG), Eco-RII (2CCWGG), NgoMIV (G2CCGGC), and Cfr10I (R2CCGGY), which recognize similar DNA sequences (as indicated, where the downward arrows denote cleavage position), share limited sequence similarity over an interrupted stretch of ϳ70 amino acid residues with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…For example, SsoII (Type IIP; |CCNGG), EcoRII (Type IIE; |CCWGG) and NgoMIV (Type IIF; G|CCGGC) have remarkably similar DNA-binding sites and catalytic centers (234). Specificities for partly related, and even unrelated, sequences can nevertheless depend upon the same structural framework: CCNGG (SsoII), CCWGG (PspGI/EcoRII), GCCGGC (NgoMIV), RCCGGY (Cfr10I), GATC (MboI) (243). …”
Section: Introductionmentioning
confidence: 99%
“…For example, SsoII (Type IIP; |CCNGG), EcoRII (Type IIE; |CCWGG) and NgoMIV (Type IIF; G|CCGGC) have remarkably similar DNA-binding sites and catalytic centers (234). Specificities for partly related, and even unrelated, sequences can nevertheless depend upon the same structural framework: CCNGG (SsoII), CCWGG (PspGI/EcoRII), GCCGGC (NgoMIV), RCCGGY (Cfr10I), GATC (MboI) (243). …”
Section: Introductionmentioning
confidence: 99%
“…Methanobrevibacter ruminantium (Euryarchaeota) forms a clade with 2 Prevotella (Bacteroidales) sequences. Methanobrevibacter ruminantium is a rumen bacterium of cattle and Prevotella is involved in periodontal infections2ixs37DpnII, MboIPF04556(91)Type II Restriction Endonuclease (91)++Prokaryota Carboxydothermus hydrogeniformans in a Mycoplasma clade. Extremophilic Dictyoglomus thermophilum (Dictyoglomi) with M. smithii & Methanosphaera stadtmanae (Euryarchaeota)38Ecl18kI, EcoRII, PspGIPF09019(92)Type II Restriction Endonuclease (92){2}+{1}Bacteria Photobacterium damselae subsp.…”
Section: Resultsmentioning
confidence: 99%
“…However, their amino acid sequences are strongly divergent. Typically, only enzymes that recognize identical or very similar DNA sequences may display similarity at the amino acid level (4). Recent bioinformatics analyses suggested that REases belong also to at least three other folds, GIY-YIG, HNH, and PLD (5-7).…”
mentioning
confidence: 99%